Aestheticism, desire, and morality: Revisiting Wilde's Dorian Gray through Tanzer's lesbian reimagining - Poorghorban, Younes (Orbis litterarum, 2025)
This paper examines the interplay of aestheticism and morality in Oscar Wilde's The Picture of Dorian Gray and Molly Tanzer's reimagining, Creatures of Will and Temper. Wilde's original narrative positions aestheticism as both a refuge and a source of ruin, interweaving themes of homoerotic desire, moral ambiguity, and societal condemnation. Through an exploration of Wilde's depiction of same‐sex desire as an inexplicable and guilt‐laden sensation, the paper contextualizes the Victorian societal constraints that shaped the novel's portrayal of queerness. In contrast, Tanzer's reinterpretation modernizes these dynamics by centering lesbianism and self‐aware queer identities. Tanzer's work introduces characters who openly embrace their sexual orientations, offering a perspective unburdened by the Victorian moral framework. However, her attempt to divorce aestheticism from morality falters, as her narrative ultimately mirrors Wilde's, with characters facing existential consequences for their indulgence in sensory pleasure. By comparing the differing treatments of queerness, aestheticism, and morality, this paper argues that Tanzer's reinterpretation simplifies the historical complexities Wilde grappled with, opting for a contemporary lens that sacrifices the tension between desire and societal constraint. Nonetheless, both works reaffirm that the pursuit of aesthetic experiences is inextricably tied to moral repercussions, whether subtle or explicit, highlighting the enduring relevance of these themes in literature.